The Influence Of Brand Image And Product Quality On The Decision To Purchase Cosmetic Products Wardah In The Case Of Gen Z - rahmat; Lubis, Dinda Arizka (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The increasingly rapid growth of the cosmetics industry in Indonesia has given rise to intense competition for every cosmetics industry. This research aims to determine the influence of brand image and product quality on purchasing decisions for Wardah products, especially among Gen Z. This type of research uses quantitative methods. The population in this study were female students from the Sharia Economics and Sharia Banking Study Program at Potential Main University with a sample size of 79 respondents. This research uses a saturated sample method. The data used in the research is primary data obtained from respondents who filled out the questionnaire and then analyzed using multiple regression analysis using SPSS-25. The research results show that the brand image variable has a significant influence on purchasing decisions for Wardah products, with a value of Sig. of 0.007 < 0.05 and Tcount 2.779 > Ttable 1.992. Apart from that, the product quality variable also shows a significant influence on purchasing decisions, with a Sig. of 0.000 < 0.05 and Tcount 6.458 > Ttable 1.992. Simultaneously, the brand image and product quality variables have a significant effect on purchasing decisions, as evidenced by the Fcount value of 103.553 > Ftable 3.117 and a significance value of 0.000. Thus, it can be concluded that brand image and product quality are important factors that influence Wardah product purchasing decisions.